Determinación de organoclorados por bioacumulación en dos especies vegetales (lactuca sativa l) y (medicago sativa) en procesos de fitorremediación en suelos agrícolas en la parroquia de Perucho del D.M.Q. en el periodo de marzo 2019 – febrero 2020. - Coyago Montaluisa, Lesly Dayana (2020)
The present investigation constitutes a phytoremediation process applied to agricultural soils in San Miguel sector of Perucho parish in the Metropolitan District of Quito (D.M.Q). The analysis allowed us to know which of the two organochlorine accumulating plant species is more environmentally friendly. The determination of bioaccumulation of organochlorines was based on the activities developed in the field together with the phase of soil sampling and the agricultural phase of the cultivation of Lactuca sativa L and Medicago sativa, which allowed the calculation of the accumulation of organochlorine substances, in order to determine the most suitable species to be used in the recovery of agricultural soils. The estimate of organochlorine accumulation of the two plant species obtained a value of <0.0002 mg/Kg in Lactuca sativa L and < 0.0002 mg/Kg in Medicago sativa, which leads to phytoremediation by plants, a feasible conventional practice for contaminated soils with high or medium level of organochlorines. The present investigation showed that both plant species are organochloride accumulators, since the practice of phytoremediation process took advantage of the capacity of plant species such as lettuce and alfalfa to absorb organochloride contaminating substances, which are from insecticides; as a result of daily use in agricultural activities, plant species are easily acquired and agricultural management does not imply greater care.